Kuantifikasi dan Karakterisasi Timbulan Sampah Makanan (Food Waste) di Pasar Tradisional Kota Surabaya Timur - Umi Hafilda Al-Hanniya; Yayok Suryo Purnomo; Aulia Ulfah farahdiba (Yayasan Literasi Sains Indonesia, 2022)
One of the new problems that arise and can have a big impact on the environment and living things is food waste. Some activities that can produce food waste, one of which is buying and selling activities in traditional markets or supermarkets. The city of Surabaya has several traditional markets that produce food waste in several areas, such as the Soponyono market and the Pacar Keling market in the East Surabaya city area. Food supply materials that are no longer fit for sale and fit for consumption are immediately transferred to temporary disposal sites (TPS) and end up as food waste. In this study, the Soponyono Market produced an average of 52.126 Kg/day of food waste with the highest category being vegetables by 78% and the Pacar Keling market of 21.887 Kg/day with the highest category being fruits by 51%. The characteristics of food waste at the Soponyono market have a water content value of 88.73% water content and 3,231.09 Cal/gr calorific value. Whereas in the Pacar Keling market, the water content is 87.44% and the calorific value is 4,222.93 Cal/gr. In this regard, it is necessary to identify the quantity and characteristics of food waste in order to find out what processing is required according to the waste produced. So that waste can be processed into energy or new useful products. The identification effort was carried out using the SNI- 19-3964-1994 method, namely by weighing and sorting food waste until the quantity, characteristics, in the form of category scope and water content value, and calorific value were known. The Soponyono market is capable of producing more and more diverse food waste than the Pacar Keling market with a different scope of categories.